Pengaruh Wisata Syariah dalam Meningkatkan Pendapatan Masyarakat di Desa Suka Jaya Batubara - Vina Arnita (ARBITRASE: Journal of Economics and Accounting, 2022)
The aim of making sharia tourism is to introduce sharia tourism in the world. Sharia tourism is very useful because the majority of Indonesia is the largest Islamic country. One of the majority is the village in coal. The natural resource in coal village is a wide river. However, the poverty rate in coal village is very high at around 75%.  The problem faced by the village is the poverty rate. Of that number, the village's poverty rate is the main problem. In addition, there are also other problems, namely the number of unemployed people in the village is relatively large, because the natural potential in the village is not utilized and livelihoods are very difficult, causing a high unemployment rate. Another problem faced by young people is that drug abuse in the village is high compared to the total population. From these problems it can be seen that the natural resources owned by this village can solve the existing problems. The village has good natural resources that can be utilized by the population. With the breadth of people's livelihoods around the riverbank tourism area, the community's income will increase and result in an increase in the community's economy. tourism area is one of the business fields that can contribute to improving the community's economy. The importance of research is carried out to develop tourist villages in Batubara Regency and provide opportunities for village communities to improve the economy.